Assays to detect beta-tubulin codon 200 polymorphism in Trichuris trichiura and Ascaris lumbricoides. - Aissatou Diawara; Lesley J Drake; Richard R Suswillo; Jimmy Kihara; Donald A P Bundy; Marilyn E Scott; Carli Halpenny; J Russell Stothard; Roger K Prichard (PLoS Neglected Tropical Diseases, 2009)
Background The soil-transmitted helminths (STH) Ascaris lumbricoides and Trichuris trichiura are gastrointestinal parasites causing many disabilities to humans, particularly children. The benzimidazole (BZ) drugs, albendazole (ALB) and mebendazole (MBZ), are commonly used for mass treatment for STH. Unfortunately, there is concern that increased use of anthelmintics could select for resistant populations of these human parasites. In veterinary parasites, and lately in filarial nematodes, a single amino acid substitution from phenylalanine to tyrosine, known to be associated with benzimidazole resistance, has been found in parasite beta-tubulin at position 200. We have developed pyrosequencer assays for codon 200 (TTC or TAC) in A. lumbricoides and T. trichiura to screen for this single nucleotide polymorphism (SNP). Method and findings Pyrosequencing assays were developed and evaluated for detecting the TTC or TAC SNP at codon 200 in beta-tubulin in A. lumbricoides and T. trichiura. Genomic DNA from individual worms, eggs isolated from individual adult worms or from fecal samples with known treatment history and origin, were sequenced at beta-tubulin by pyrosequencing, and genotypes were confirmed by conventional sequencing. The assays were applied to adult worms from a benzimidazole-naïve population in Kenya. Following this, these assays were applied to individual worms and pooled eggs from people in East Africa (Uganda and Zanzibar) and Central America (Panama) where mass anthelmintic drug programs had been implemented. All A. lumbricoides samples were TTC. However, we found 0.4% homozygous TAC/TAC in T. trichiura worms from non-treated people in Kenya, and 63% of T. trichiura egg pools from treated people in Panama contained only TAC. Conclusion Although the codon 200 TAC SNP was not found in any of the A. lumbricoides samples analyzed, a rapid genotyping assay has been developed that can be used to examine larger populations of this parasite and to monitor for possible benzimidazole resistance development. The TAC SNP at codon 200, associated with benzimidazole resistance in other nematodes, does occur in T. trichiura, and a rapid assay has been developed to allow populations of this parasite to be monitored for the frequency of this SNP. Sample sizes were small, anthelmintic efficacy was not assessed, and treated and non-treated samples were from different locations, so these frequencies cannot be extrapolated to other populations of T. trichiura or to a conclusion about resistance to treatment. The occurrence of the TAC SNP at codon 200 of beta-tubulin in T. trichiura may explain why benzimidazole anthelmintics are not always highly effective against this species of STH. These assays will be useful in assessing appropriate treatment in areas of high T. trichiura prevalence and in monitoring for possible resistance development in these STH.